An amino-decorated dual-functional metal–organic framework for highly selective sensing of Cr(iii) and Cr(vi) ions and detection of nitroaromatic explosives. Issue 40 (22nd September 2016) - Lv, Rui; Wang, Jingyao; Zhang, Yanping; Li, Hui; Yang, Linyan; Liao, Shengyun; Gu, Wen; Liu, Xin
Abstract : A 3D NH2 –Zn-MOF has been successfully constructed via a hydrothermal reaction. It exhibits high selectivity and sensitivity towards Cr(iii ), Cr(vi ) ions and nitroaromatic compounds. Abstract : A 3D Zn(ii )-based metal-organic framework, [Zn2 (TPOM)(NH2 –BDC)2 ]·4H2 O (NH2 –Zn-MOF, TPOM = tetrakis(4-pyridyloxymethylene)methane and NH2 –BDC = 2-aminoterephthalic acid), was successfully achieved via a hydrothermal reaction. The framework adopts a (4, 2)-connected 3D network, with the Schläfli symbol {6 2 ·8 4 }. This complex exhibits strong luminescence emission, which is selectively sensitive to Cr(iii ) and Cr(vi ) ions. More importantly, the fluorescence explorations indicated that it represents the first example of MOF-based fluorescent probes for detecting Cr(iii ) through a fluorescence enhancement mechanism. In addition, it also shows highly selective and sensitive detection of electron-deficient nitroaromatic compounds through fluorescence quenching. These properties make the NH2 –Zn-MOF a potential luminescence sensor for selectively detecting these chemicals.